Fostering reflection in the EFL classroom - Mesa Solano, Viviana; León Posada, Geidy Yohana (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article shares a pedagogical experience that attempted to foster reflective and interactive activities in our English lessons development. Besides, it describes some of the resources that learners used to express their ideas critically. From our research experience, it was evidenced that teachers focusedmainly in achieving students’ linguistic development. The main discussion of this study refers to the necessity of implementing new perspectives of teaching where language is taken as a social practice to foster reflective thinking through our pedagogical practices. Therefore, we as teachers should generate a confidentenvironment in order to promote students’ reflection and interaction in a spontaneous way. Those learning opportunities are